PWE-068 Higher Diagnostic Yield, Younger Age and Improved Performance Status at Diagnosis Associated with The National Oesophago-Gastric (OG) Awareness Campaign (2015) – A District General Hospital Perspective. (17th August 2016) - Coombs, CA; Pope, L; O'Donnell, M; Pearl, DS
Abstract : Introduction: A retrospective study evaluating the impact of the English national oesophageal and gastric cancer awareness campaign (26/01/2015-22/02/2015) on a large district general hospital (DGH). The campaign involved radio and television broadcasts advising medical assessment for dysphagia or persistent dyspepsia. Methods: Data from all two week wait (2 ww) OG referrals triaged to gastroscopy (OGD) from January to July in 2014 and 2015, was audited retrospectively. The Somerset Cancer Register (SCR) database was used for data collection. Age and World Health Organisation (WHO) performance status, recorded at point of referral, was retrieved from the SCR. Number of referrals, cancer diagnoses, age, WHO performance status and treatment intent were compared between an identical 6 month period in 2014 and 2015. Formal statistical analysis was not carried out. Results: There was a 26% increase in 2 ww referrals from 2014 to 2015 (530 to 667) and 4% in non 2 ww referrals (477 to 496). The number and percentage (%yield) of OG cancer diagnoses from 2 ww referrals was 27 (5.0%) in 2014 compared to 32 (4.8%) in 2015. The number and percentage (%yield) of OG cancer diagnoses from routes other than 2 ww OG referral was 17 (3.6%) in 2014 compared to 26 (5.2%) in 2015. The mean and median age at diagnosis expressed in years was 77 and 79 (2014) compared with 69 and 75 (2015). Of OG cancer diagnoses, the treatment intent was considered potentially curative in 33% (2014) compared with 34% (2015). Percentage of patients recorded as WHO performance status 0 and 1 combined was 74% (2014) compared to 91% (2015). One year mortality data is not yet available due to early reporting. Conclusion: The 26% increase in 2 ww OG referrals is likely to be heavily influenced by the national OG awareness campaign, on the background of an 11% per annum increase in demand for diagnostic endoscopy services. Interestingly the percentage of cancer findings at OGD remained around 5% indicating that the increased diagnostic throughput has translated to OG cancer diagnoses. The mean and median age at diagnosis was 8 and 4 years lower respectively; this may indicate earlier patient directed self-referral to primary care with OG symptoms, suggesting that the campaign has reached its target audience. Unfortunately, there was not been an obvious increase in potentially curative OG cancer diagnoses; however, the younger group and better performance status may support more intense oncological therapy, leading to improved outcomes. Disclosure of Interest: None Declared